New Trend of Modern Siraiki Poetry - Khan, Badar Masood; Mai, Naseem; Saeed, Saima (sourcecoder, 2023)
Different aspects of poetry have their unique identity. Every verse has a great impact on human life different dimensions of expression have brought marvelous changes in society. Love for the country and the Dharti where he has born is the land of heaven for the poet. There are many dreams in these writings. True picture of rusty and dusty people has become clear. Their lust for wealth and wish for everything made them Animals. So called religions mulaan make it so difficult for common people their love and attachment towards their lord. The only creator Allah Almighty lives in their hearts; it is the message of the day. Siraiki wasib is land of selfless people. They love their internal hobbit. They have never lust for the wealth from unfair means.